THE ROLE OF SUNK COSTS IN ENTRY PROCESS INTO A FOREIGN MARKET: THEORETICAL APPROACH - K. Nadtochii (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The category of sunk costs is studied along with specific features of entry barriers. Different scientific approaches in defining a category are compared to make author's own. The study elucidates a role of sunk costs, including its influence on researching a market, evaluating an efficiency of entering into market and evaluating its risk. The paper highlights three main components of sunk costs, that are: investments to reduce production costs of incumbents relative to newcomers, investments to change a structure of rival's costs and investments to positive change of a demand on a product. Author proposes to consider sunk costs as a strategic barrier, due to a huge influence of incumbents' activities. A need to invest these costs also determines a high competitiveness of a new firm.